Comprehensive Evaluation of Hemostasis in Normal Women: Impact on the Diagnosis of Mild Bleeding Disorders. (January 2015) - MacEachern, Kimberly; Kaur, Harmanpreet; Toukh, Mazen; Mumal, Iqra; Hamilton, Alexander; Scovil, Stephen; James, Paula; Elbatarny, Hisham S.; Othman, Maha
Women with mild bleeding disorders (MBDs) pose a diagnostic challenge and menorrhagia, the most common presenting symptom that remains underreported. We tested the hypothesis that screening apparently normal females using general and gynecological bleeding assessment tools and a global hemostatic assay together with platelet aggregation can help predict MBDs. We assessed 47 women using electronic bleeding assessment tools; e-bleeding questionnaire; and e-Pictorial Bleeding Assessment Chart (e-PBAC) based on previously validated methods, thrombelastography (TEG), and platelet aggregation together with basic coagulation testing. Three women had elevated bleeding score with von Willebrand disease diagnosis confirmed in one case and eleven cases had elevated e-PBAC. We report normal ranges for TEG and platelet aggregation in women during the first half of the menstrual cycle and show 23.4% of apparently normal women may have general or heavy menstrual bleeding. This is a prelude to a larger study to determine the validity of bleeding assessment tools in screening for MBDs in women.